3D printing preparation method of high-absorption electromagnetic shielding composite material with gradient structure
The high absorption electromagnetic shielding composite material with gradient structure was prepared through 3D printing technology, which solved the problem of secondary electromagnetic radiation pollution caused by electromagnetic wave reflection in existing materials, and achieved the combination of high EMI shielding and excellent mechanical properties.
Patent Information
- Application Number
- CN202411953521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing conductive electromagnetic interference shielding composite materials have severe secondary electromagnetic radiation pollution due to their electromagnetic wave reflection characteristics.
3D printing technology is used to prepare a high-absorbing electromagnetic shielding composite material with a gradient structure. Through the combination of Fe3O4/CNT/PU composite ink and a highly conductive flexible MXene film, a multi-hole structure and a double-gradient structure are formed to achieve the absorption and shielding of electromagnetic waves.
The high EMI shielding performance and excellent mechanical properties of composite materials are achieved, which reduces secondary electromagnetic radiation pollution and has asymmetric and adjustable high absorption coefficient.
Smart Images

Figure CN119684779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of electromagnetic shielding composite materials, and in particular to a 3D printing preparation method of a high-absorption electromagnetic shielding composite material with a gradient structure. Background Art
[0002] With the rapid development of human society and the widespread application of modern electronic communication technology, in order to ensure the normal operation of precision electronic devices and human health, it is necessary to develop ultra-high-efficiency electromagnetic interference (EMI) shielding materials with lightweight and flexible customizable structures. Compared with traditional metal-based electromagnetic shielding materials with poor processing performance, high density and easy corrosion, polymer-based magneto-electric composites have been rapidly developed in multiple application fields due to their corrosion resistance, easy processing and flexible magneto-electric network design. In general, various conductive fillers, such as two-dimensional (2D) transition metal carbides / nitrides (MXene), carbon nanotubes (CNTs), graphene, metal nanowires, etc., have been incorporated into polymers to manufacture high-performance EMI shielding polymer composites.
[0003] However, these conductive EMI shielding composites have obvious electromagnetic wave (EMW) reflection characteristics, which leads to serious secondary electromagnetic radiation pollution. Therefore, in order to minimize the secondary electromagnetic radiation pollution, it is urgent to develop high electromagnetic shielding polymer-based composites based on electro-magnetic networks with absorption as the main method for the next generation of electronic devices. Summary of the invention
[0004] In order to solve the problem of how to reduce the serious secondary electromagnetic radiation pollution caused by the electromagnetic wave (EMW) reflection characteristics of existing conductive electromagnetic interference shielding composite materials, the present invention provides a 3D printing preparation method of a high-absorption electromagnetic shielding composite material with a gradient structure.
[0005] In a first aspect, the present invention provides a 3D printing preparation method of a high-absorption electromagnetic shielding composite material with a gradient structure, the preparation method comprising:
[0006] Step 1: Fe 3 O 4 Preparation and collection of / CNT / PU composite ink: Fe 3 O 4 Add CNT to dimethyl sulfoxide solution, shake well and perform ultrasonic dispersion for 25-35 min, then continue to add TPU particles and continue mechanical stirring at room temperature for 11-13 hours to obtain Fe 3 O 4 / CNT / PU composite ink, add different CNT content as needed to configure a variety of Fe 3 O 4 / CNT / PU composite ink;
[0007] Step 2: Preparation of a composite framework with a porous structure: The various Fe 3 O 4 The CNT / PU composite ink is sequentially input into a 3D printer for extrusion printing in a coagulation bath to obtain a composite frame with a three-dimensional gradient structure, and the composite frame is soaked and rinsed with deionized water, and then dried at a constant temperature to obtain a composite frame with a porous structure;
[0008] Step 3: Preparation of a high-absorption electromagnetic shielding composite material with a gradient structure: The composite frame with a porous structure prepared above is bonded and cured using a polyurethane solution and a highly conductive flexible MXene film obtained by vacuum filtration to obtain a high-absorption electromagnetic shielding composite material with a gradient structure.
[0009] In some embodiments, the composite frame is formed by stacking a plurality of structural frames with different lattice scales from bottom to top, wherein the lattice scales of the plurality of structural frames are successively increased, and each of the structural frames is composed of one of the Fe 3 O 4 / CNT / PU composite ink was made by immersion precipitation 3D printing. 3 O 4 The CNT content of the / CNT / PU composite ink shows a decreasing trend in sequence, and the highly conductive and flexible MXene film is bonded to the bottom of the composite frame and is located on the surface of the side where the structural frame with the smallest lattice scale is located.
[0010] In some embodiments, the composite frame is soaked and rinsed in ionized water at least 2 to 3 times.
[0011] In some embodiments, the composite frame is dried at a constant temperature for at least 10 hours, and the temperature of the constant temperature ranges from 32°C to 45°C.
[0012] In some embodiments, the lattice scale difference between two adjacent structural frames ranges from 0.05 mm to 1 mm.
[0013] In some embodiments, the method for preparing the highly conductive flexible MXene film comprises the following steps:
[0014] (1) LiF and hydrochloric acid are mixed and placed in a water bath with a temperature of ≤42°C with magnetic stirring;
[0015] (2) Add Ti 3 AlC 2 Powder and heat to ≥45°C, continue stirring for 48-72h;
[0016] (3) centrifuging the reaction solution at 4500-5500 rpm for ≥2 min and removing the supernatant;
[0017] (4) adding hydrochloric acid, ultrasonically treating for ≥5 min and centrifuging for a second time at 4500-5500 rpm, washing with water and centrifuging for ≥5 times, and the solution is neutral, i.e., pH ≥5. After the reaction is completed, placing in an ice water bath and ultrasonically dispersing for ≥2 h;
[0018] (5) high-speed centrifuging the MXene solution obtained in step (4) to obtain a dispersion of few-layer MXene nanosheets;
[0019] (6) The few-layer MXene nanosheet dispersion obtained in step (5) is subjected to vacuum-assisted filtration to prepare the highly conductive and flexible MXene film.
[0020] In some embodiments, the flexible MXene film has an average thickness of 12 μm and an electrical conductivity of 3.1×10 5 S / m.
[0021] In some embodiments, the Fe 3 O 4 The mass ratio of CNT and TPU particles is 1:0 to 1:8.5 to 9.5.
[0022] In some embodiments, the Fe 3 O 4 The CNT content in the / CNT / PU composite ink is 0wt% to 8.9wt%.
[0023] In some embodiments, the conductivity between two adjacent structural frames varies in the range of 1×10 -8 ~3.1×10 5 S / m.
[0024] In order to solve the problem of how to reduce the serious secondary electromagnetic radiation pollution caused by the electromagnetic wave (EMW) reflection characteristics of the existing conductive electromagnetic interference shielding composite materials, the present invention has the following advantages:
[0025] Through the technical solution of the present invention, a high-performance electromagnetic interference (EMI) shielding flexible composite material with excellent mechanical properties and absorption-based performance is provided. The immersion deposition 3D printing technology is used to continuously and accurately control the printing wire spacing, i.e., the lattice scale, from bottom to top in the solidification bath, and at the same time adjust the Fe 3 O 4The content of conductive filler CNT in the / CNT / PU composite ink obtains a layered and porous composite framework, which is further bonded and assembled with a highly conductive flexible MXene film to obtain a high-absorption electromagnetic shielding composite material with a gradient structure, achieving high EMI shielding and excellent mechanical properties with asymmetric adjustable absorption coefficients (A) on the front and back sides of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic flow chart of a method for preparing a high-absorption electromagnetic shielding composite material with a gradient structure is shown;
[0027] Figure 2 (a) shows a multilayer Ti 3 C 2 SEM micrograph of Tx;
[0028] Figure 2 (b) shows the peeled Ti 3 C 2 SEM micrograph of Tx nanosheets;
[0029] Figure 2 (c) shows the exfoliated Ti 3 C 2 TEM images of Tx nanosheets.
[0030] Figure 2 (d) shows a flexible Ti with a thickness of about 12 μm and bending flexibility properties. 3 C 2 Digital image of Tx film;
[0031] Figure 2 (e) shows a schematic diagram of the top layer of DGFCP&M-10 lightweight composite material;
[0032] Figure 2 (f) shows a schematic diagram of the cross section of the 5th to 10th layers of the DGFCP&M-10 lightweight composite material;
[0033] Figure 2 (g) shows the SEM micrographs of layers 1-4 with MXene films;
[0034] Figure 2 (h) shows a schematic diagram of the cross section of a DGFCP&M-10 lightweight composite monofilament;
[0035] Figure 2 (i) shows Figure 2 (h) SEM micrograph of the enlarged part;
[0036] Figure 2(j) shows an EDS image of a partial cross section of the DGFCP&M-10 lightweight composite material;
[0037] Figure 3 (a) shows the schematic diagram of the structure of the grid-filled dual-gradient DGFCP&M-10 lightweight composite material;
[0038] Figure 3 (b) shows a schematic diagram Figure 3 (a) Schematic diagram of the lightweight composite X-band EMISET shown;
[0039] Figure 3 (c) shows a schematic diagram Figure 3 (a) The average SE of the lightweight composite material T , SE A , SE R value;
[0040] Figure 3 (d) shows a schematic diagram Figure 3 (a) The values of A, R, and T coefficients of the lightweight composite material shown;
[0041] Figure 3 (e) shows a schematic structural diagram of a single gradient SGFCP&M-10 composite material;
[0042] Figure 3 (f) shows a schematic diagram Figure 3 (e) Schematic diagram of the composite material x-band EMISET shown;
[0043] Figure 3 (g) shows a schematic diagram Figure 3 (e) The average SE of the composite material shown T , SE A , SE R value;
[0044] Figure 3 (h) shows a schematic diagram Figure 3 (e) A, R, and T coefficient values of the composite materials shown;
[0045] Figure 3 (i) shows the schematic structural diagram of the non-gradient FCP&M-10 composite material;
[0046] Figure 3 (j) shows a schematic diagram Figure 3 (i) Schematic diagram of the composite X-band EMISET shown;
[0047] Figure 3 (k) shows a schematic diagram Figure 3 (i) The average SE of the composites shown T , SEA , SE R value;
[0048] Figure 3 (l) shows a schematic diagram Figure 3 (i) A, R, and T coefficient values of the composite materials shown. DETAILED DESCRIPTION
[0049] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.
[0050] As used herein, the term "including" and its variants are to be interpreted as open-ended terms meaning "including but not limited to". The term "based on" is to be interpreted as "based at least in part on". The terms "one embodiment" and "an embodiment" are to be interpreted as "at least one embodiment". The term "another embodiment" is to be interpreted as "at least one other embodiment". The orientation or position relationship indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like is based on the orientation or position relationship shown in the accompanying drawings. These terms are mainly for better describing the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation. In addition, in addition to being used to indicate an orientation or position relationship, some of the above terms may also be used to indicate other meanings, such as the term "upper" may also be used to indicate a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to the specific circumstances. In addition, the terms "install", "set", "provided with", "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be directly connected, or indirectly connected through an intermediate medium, or it can be an internal connection between two devices, elements or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0051] According to research, the reasonable distribution of magneto-electric synergistic networks can improve the absorption and dissipation of electromagnetic waves by polymer-based materials. At the same time, adding structural design (such as isolation structure, foam structure and gradient structure, etc.) to electro-magnetic synergistic polymer-based composite materials has been widely adopted and has become a popular strategy to enhance absorption and electromagnetic interference shielding performance. Therefore, through a flexible and simple strategy, the combination of filler functions and structural design of polymer-based electromagnetic interference shielding materials have important practical significance for the development of lightweight materials with good mechanical, high absorption and high electromagnetic interference shielding performance.
[0052] 3D printing technology has significant advantages such as controllable design, easy construction of complex structures and precise integration of multiple components, which has a significant impact on the optimized design and controlled manufacturing processes in the fields of aerospace, electronics and biomedicine. In recent years, DIW3D printing technology has been successfully applied in many fields such as biomedicine, microelectronic devices and electrochemical energy storage due to its advantages such as flexible structural customization and simple operation. Among them, a DIW3D printing method based on a polymer-solvent-nonsolvent (PS-NS) ternary system (called immersion precipitation 3D printing, ip3DP) provides the ability to use inks with a wide range of viscosities to manufacture 3D porous models, and acts as a useful toolkit in the 3D printing of hierarchical structures and functional scaffolds, which is expected to become a new strategy for the integrated customized preparation of highly absorbing and highly electromagnetic interference shielding polymer-based materials.
[0053] Therefore, the present application discloses a 3D printing preparation method of a high absorption electromagnetic shielding composite material with a gradient structure, such as Figures 1 to 3 As shown in (l), the preparation method comprises:
[0054] Step 1: Preparation and collection of Fe3O4 / CNT / PU composite ink: 3 O 4 Add CNT to dimethyl sulfoxide solution, shake well and perform ultrasonic dispersion for 25-35 min, then continue to add TPU particles and continue mechanical stirring at room temperature for 11-13 hours to obtain Fe 3 O 4 / CNT / PU composite ink, add different CNT content as needed to configure a variety of Fe 3 O 4 / CNT / PU composite ink;
[0055] Step 2: Preparation of a composite framework with a porous structure: The various Fe 3 O 4The CNT / PU composite ink is sequentially input into a 3D printer for extrusion printing in a coagulation bath to obtain a composite frame with a three-dimensional gradient structure, and the composite frame is soaked and rinsed with deionized water, and then dried at a constant temperature to obtain a composite frame with a porous structure;
[0056] Step 3: Preparation of a high-absorption electromagnetic shielding composite material with a gradient structure: The composite frame with a porous structure prepared above is bonded and cured using a polyurethane solution and a highly conductive flexible MXene film obtained by vacuum filtration to obtain a high-absorption electromagnetic shielding composite material with a gradient structure. In the present application, the high-absorption electromagnetic shielding composite material with a gradient structure also has excellent mechanical properties.
[0057] Furthermore, the composite frame is formed by stacking a plurality of structural frames with different lattice scales from bottom to top, the lattice scales of the plurality of structural frames are in an increasing trend, and each of the structural frames is composed of one of the Fe 3 O 4 / CNT / PU composite ink was made by immersion precipitation 3D printing. 3 O 4 The CNT content of the Fe / CNT / PU composite ink decreases in turn, so that each of the Fe 3 O 4 The electrical conductivity of the / CNT / PU composite ink shows a decreasing trend from bottom to top. The highly conductive flexible MXene film is bonded to the bottom of the composite frame and is located on the surface of the side where the structural frame with the smallest lattice scale is located.
[0058] Furthermore, the composite frame is soaked and rinsed with ionized water at least 2 to 3 times.
[0059] Furthermore, the composite frame is dried at a constant temperature for at least 10 hours, and the temperature of the constant temperature ranges from 32°C to 45°C.
[0060] Furthermore, the lattice scale difference between two adjacent structural frames ranges from 0.05 mm to 1 mm.
[0061] Furthermore, the method for preparing the highly conductive flexible MXene film comprises the following steps:
[0062] (1) LiF and hydrochloric acid are mixed and placed in a water bath with a temperature of ≤42°C with magnetic stirring;
[0063] (2) Add Ti3AlC2 powder and raise the temperature to ≥45°C, and continue stirring for 48 to 72 hours;
[0064] (3) centrifuging the reaction solution at 4500-5500 rpm for ≥2 min and removing the supernatant;
[0065] (4) adding hydrochloric acid, ultrasonically treating for ≥5 min and centrifuging for a second time at 4500-5500 rpm, washing with water and centrifuging for ≥5 times, and the solution is neutral, i.e., pH ≥5. After the reaction is completed, placing in an ice water bath and ultrasonically dispersing for ≥2 h;
[0066] (5) high-speed centrifuging the MXene solution obtained in step (4) to obtain a dispersion of few-layer MXene nanosheets;
[0067] (6) The few-layer MXene nanosheet dispersion obtained in step (5) is subjected to vacuum-assisted filtration to prepare the highly conductive and flexible MXene film.
[0068] Furthermore, the average thickness of the flexible MXene film is 12 μm, and the electrical conductivity is 3.1×10 5 S / m.
[0069] Furthermore, the Fe 3 O 4 The mass ratio of CNT and TPU particles is 1:0 to 1:8.5 to 9.5.
[0070] Furthermore, the Fe 3 O 4 The CNT content in the / CNT / PU composite ink is 0wt% to 8.9wt%.
[0071] Furthermore, the conductivity variation range between two adjacent structural frames is 1×10 -8 ~3.1×10 5 S / m.
[0072] This application provides a method for preparing a high-absorption electromagnetic shielding composite material with a gradient structure by using a flexible and simple vacuum filtration process assisted immersion precipitation 3D printing technology (ip3DP). First, by using a 3D printing technology with an integrated multi-nozzle extrusion control system, the printing wire spacing is precisely controlled from bottom to top in a coagulation bath, and the Fe 3 O 4The CNT content in the / CNT / PU ink is lightened and has a porous composite framework. Furthermore, the porous composite framework is bonded and assembled with the highly conductive flexible MXene film obtained by the vacuum filtration process to form a high-absorption electromagnetic shielding composite material with a dual gradient structure design. Among them, a lightweight and porous structural framework with a large-scale lattice printed with a magnetic low-conductivity ink is used as the electromagnetic absorption layer, i.e., the impedance matching layer, on the top of the composite framework, while a lightweight and porous structural framework with a small-scale lattice printed with a magnetic high-conductivity ink is used as the bottom structure of the composite framework and bonded and assembled with an ultra-high conductive MXene film as an electromagnetic reflection layer, forming a "weak reflection-absorption-strong reflection-reabsorption" interface. In addition, the microscopic porous structure inside the composite framework further limits the incident wave from penetrating the material in a specific direction, and dissipates the electromagnetic wave through multiple reflections at the rich interface, effectively expanding the dissipation path of the electromagnetic wave. As expected, thanks to the synergistic effect of polymer PU with excellent mechanical properties and fillers, the DGFCP&M lightweight composite frame has a high EMISE of 72.7dB and a high absorption coefficient A of 0.62, as well as an excellent elongation at break of up to 128% and a tensile strength of 2.2MPa.
[0073] The present invention provides a new idea for developing lightweight materials with excellent mechanical properties, low reflection and high electromagnetic interference shielding performance, and has broad application prospects in multiple high-end electromagnetic shielding fields such as biological health protection, ultra-precision electronic components and aerospace.
[0074] Preparation of highly conductive flexible MXene films;
[0075] Among them, Ti was etched in LiF / HCl solution 3 AlC 2 phase, followed by ultrasonic exfoliation to obtain layered MXene, which was then combined with vacuum-assisted filtration to prepare highly conductive and flexible MXene films.
[0076] The specific preparation process is as follows: First, lithium fluoride (2 g) is added to hydrochloric acid (40 mL, 9 mol·L -1 ) and stirred in a 42°C water bath with magnetic stirring for 30 min at a speed of 600 r / min -1 .
[0077] Subsequently, 2 g Ti3AlC2 powder was gradually added to the above solution, and the mixed solution was continuously stirred in a 45 °C water bath for 48 h for etching. The etched solution was centrifuged at 5000 rpm for 5 min to remove the supernatant, and a certain amount of hydrochloric acid (1 mol·L -1 ), shake well and then perform ultrasonic treatment, wherein the ultrasonic power is 350 W and the ultrasonic time is 10 min; then perform secondary centrifugation at 5000 rpm for 5 min.
[0078] Then, a water washing centrifugal expansion treatment was adopted, that is, the multilayer MXene was repeatedly washed 8-10 times with deionized water by the expansion principle of high-speed centrifugation (i.e., three centrifugations at a speed of 5000 rpm for 1 min) until the solution pH was ≥5.
[0079] Subsequently, the precipitate was ultrasonically dispersed in deionized water in an ice-water bath for 2 hours, and the MXene solution was collected and centrifuged at 3500 rpm for 30 minutes to obtain a black-brown supernatant, which was the dispersion of few-layer MXene nanosheets.
[0080] Finally, take 5 ml of the few-layer MXene dispersion (12 mg mL -1 ), and a high-conductive flexible MXene film of a certain thickness is prepared by vacuum-assisted filtration. In the present application, the average thickness of the high-conductive flexible MXene film is preferably 12 μm, and its conductivity is 3.1×10 5 S / m.
[0081] Fe 3 O 4 Preparation of / CNT / PU composite ink;
[0082] First, 0.4 g of Fe with a solid content of 8.9 wt% was added. 3 O 4 0.2 g of CNT (carbon nanotube) with a solid content of 4.5 wt% was added to 20 ml of dimethyl sulfoxide solution, shaken thoroughly and subjected to ultrasonic dispersion for 30 min, and then 3.88 g of TPU particles with a solid content of 86.6 wt% were added and mechanically stirred continuously at room temperature for 12 hours to obtain Fe 3 O 4 / CNT / PU-4.5 composite ink (named FCP-4.5).
[0083] By changing the content of CNT, inks with different CNT contents are obtained. According to different CNT contents, such as 0wt%, 2.3wt%, 4.5wt%, 6.7wt% and 8.9wt%, the composite ink is named FCP-x, where x takes values of 0, 2.3, 4.5, 6.7 and 8.9.
[0084] ip3DP process and manufacturing process of high absorption electromagnetic shielding composite materials with gradient structure;
[0085] The prepared FCP-x composite ink was loaded into independent syringes respectively, and a self-built 3D printer with integrated multi-nozzle extrusion control was used to perform customized structure printing in combination with air pressure drive control extrusion. The needle specification selected for printing is 23G, i.e., a diameter of 0.3mm. The needle is immersed in a coagulation bath, i.e., an aqueous solution of DMSO with a solid content of 50wt%, wherein the coagulation bath is placed in a plastic culture dish made of polystyrene, which effectively ensures the reliable adsorption of the bottom extruded filaments to the surface of the culture dish. In this application, the structural framework ".gcode" files of different lattice scales can be generated in advance through MATLAB software programming, and then they are successively imported into the 3D printer control software RepetierHost to execute the motion control program, and the molding accuracy of the extruded filaments is controlled by adjusting the pressure value of the air pressure drive, and the free switching of the printing ink is realized through the multi-nozzle extrusion control system. In this embodiment, four dual-gradient (i.e., lattice size and conductive filler content) structural frameworks are constructed, named "dual gradient Fe 3 O 4 / CNT / PU&MXene-y(DGFCP&M-y)", wherein y refers to the number of printed layers of the composite frame, and preferably takes values of 4, 6, 8, and 10, but this application is not limited to this.
[0086] In this embodiment, a typical dual-gradient lightweight composite material frame preparation process is selected for introduction.
[0087] First, we use FCP-8.9 composite ink to print the first and second layers of lattice structure, with a lattice scale of 0.3mm, that is, by adjusting the spacing and arrangement of the printed wire strips, the printed structure of the structural frame is obtained. The adjacent wire strips of the first layer are arranged at intervals of 0.3mm, and the second layer is arranged perpendicular to the first layer, and the adjacent wire strips are also arranged at intervals of 0.3mm; then switch to FCP-6.7 ink to print the third and fourth layers of lattice structure, with a lattice scale of 0.4mm, that is, the third layer of wire strips is arranged parallel to the first layer, and the spacing between adjacent wire strips of the third layer is 0.4mm. The fourth layer is arranged in the same way as the third layer, but the arrangement direction is perpendicular to the third layer; then switch to FCP-4.5 ink to print the fifth and sixth layers of lattice structure, with a lattice scale of 0.5mm, that is, the fifth The arrangement of the layer of wire strips is parallel to the third layer, the spacing between adjacent wire strips in the fifth layer structure is 0.5mm, the arrangement of the sixth layer is the same as the fifth layer, but the arrangement direction is perpendicular to the fifth layer; switch to FCP-2.3 ink to print the seventh and eighth lattice structures, the lattice scale is 0.6mm, that is, the arrangement of the seventh layer of wire strips is parallel to the fifth layer, the spacing between adjacent wire strips in the seventh layer structure is 0.6mm, the arrangement of the eighth layer is the same as the seventh layer, but the arrangement direction is perpendicular to the seventh layer; switch to FCP-0 ink to print the ninth and tenth lattice structures, the lattice scale is 0.7mm, that is, the arrangement of the ninth layer of wire strips is parallel to the seventh layer, the spacing between adjacent wire strips in the ninth layer structure is 0.7mm, the arrangement of the tenth layer is the same as the ninth layer, but the arrangement direction is perpendicular to the ninth layer, and a composite framework with a three-dimensional gradient structure is obtained. In this application, the coagulation bath used for printing is a dimethyl sulfoxide (DMSO) aqueous solution with a concentration range of 30%-60%.
[0088] Secondly, the printed composite frame was repeatedly soaked and rinsed with deionized water for 4 to 5 times to ensure the full non-solvent induced phase separation process and remove the residual DMSO solvent.
[0089] Subsequently, the structural support was placed in a vacuum drying oven at 38°C for continuous drying for 12 hours to obtain a composite frame with multiple layers of different porous structures.
[0090] Finally, the highly conductive flexible MXene film coated with a polyurethane solution was bonded and cured to the surface of the first layer printed in the dried composite frame to obtain a highly absorptive electromagnetic shielding composite material with a gradient structure.
[0091] The Fe2+ nanotubes with different contents were synthesized by ip3DP technology. 3 O 4 / CNT / PU ink is precisely extruded and continuously printed in a coagulation bath to obtain a lightweight composite framework with excellent consistency and stability of surface lattice size. Figure 2(f) It can be seen that with the gradient change of the size of the printing lattice, the macroscopic spacing of the printed wires of the DGFCP&M-y composite material gradually increases from 0.3mm to 0.7mm. At the same time, with the gradient change of the carbon nanotube content during the printing process, the color of the DGFCP&M-y composite material gradually changes from dark black to light gray, and the composite frame of the three-dimensional gradient structure also forms a multi-layer porous structure, that is, each layer of the wire of each structural frame also has a large number of hole structures. By changing the concentration of the carbon nanotube content during the printing process, the wire of each structural frame has a hole structure with different pores, so that the composite frame with a three-dimensional gradient structure forms a composite frame with a multi-porous structure, and then the existing conductive electromagnetic interference shielding composite material has a large number of reflected electromagnetic waves due to the electromagnetic wave (EMW) reflection characteristics. Enter the composite frame with a porous structure for multi-interface electromagnetic wave reflection dissipation.
[0092] In addition, since the polymer PU has a strong hydrogen bonding effect in the FCP-x composite ink, it effectively ensures the good connection between the two adjacent layers of printed wires. Figure 2 (g) to Figure 2 (h) shows that the 3D printed extruded filaments undergo phase separation in the coagulation bath, and different components undergo segregation and enrichment, ultimately forming a rich porous structure at the filament interface, in which the PU polymer phase separates to form a continuous matrix phase, and the CNT and Fe 3 O 4 The fillers are concentrated in the pores, resulting in the porous structure of the DGFCP&M-y lightweight composite material consisting of a gradient macroscopic lattice pore structure and a continuous microscopic porous structure. In addition, the lightweight composite frame and the flexible MXene film obtained by vacuum filtration were bonded and assembled with a polyurethane adhesive to obtain a porous structure DGFCP&M-y lightweight composite material with dual gradients of lattice size and conductive fillers.
[0093] The electromagnetic shielding performance of DGFCP&M-y lightweight composite material is specifically manifested in that the ip3DP technology integrated with a multi-nozzle extrusion control system is used to construct a DGFCP&M-y lightweight composite material with dual gradients of lattice size and filler. The composite framework of the DGFCP&M-y lightweight composite material is based on the gradient change of the lattice size to maintain the Fe 3 O 4The content of magnetic filler remains unchanged, and the content of conductive filler carbon nanotubes is controlled to adjust the conductivity of each layer of the printed bracket. Combined with the ultra-high conductive flexible MXene film at the bottom (conductivity: 3.1×105S·m-1), the gradient conductivity of the composite material from the top layer to the bottom layer is achieved. When the carbon nanotube content of the FCP-x (x=0, 2.3, 4.5, 6.7, 8.9, representing the mass fraction of carbon nanotubes) ink used for multi-material 3D printing increases from 2.3wt% to 8.9wt%, the conductivity increases from 0.16 to 18.1S·m-1, and the conductive performance is improved by about 113 times. The top two layers of the structure are printed with FCP-0 ink according to the lattice size of 0.7mm as the impedance matching layer. The bottom two layers of the structure are printed with FCP-8.9 ink according to the lattice size of 0.3mm, and bonded with the flexible MXene film to form an impedance mismatch layer. The intermediate layer structures were printed as transition layers using FCP-2.3, FCP-4.5, and FCP-6.7 inks with lattice sizes of 0.4 mm, 0.5 mm, and 0.6 mm, respectively.
[0094] For comparison, this application also discloses a single lattice gradient Fe 3 O 4 / CNT / PU&MXene-y(SGFCP&M-y) and uniform non-gradient Fe 3 O 4 / CNT / PU&MXene-y (FCP&M-y) composite materials. Both FCP&M and SGFCP&M composite materials are derived from FCP-4.5 composite ink to ensure that carbon nanotubes and Fe 3 O 4 The content of the same. With the increase of the number of printed layers, the average thickness of the FCP&M composite increased from 0.9mm to 2.1mm, while the lattice size of each layer was set to a constant 0.5mm. Similarly, the SGFCP&M composite also showed an increase in average thickness (1.0-2.1mm) with the increase of the number of printed layers and the gradient lattice size (0.4-0.7mm) from bottom to top.
[0095] In order to highlight the DGFCP&M's "lattice-filler" grid-filled dual-gradient architecture composite material (i.e. Figure 3 (a) shows) has the advantage of enhancing EMI shielding performance, the present application also discloses a single grid lattice gradient SGFCP&M-y (i.e. Figure 3 (c)) and uniform FCP&M-y (and Figure 3 (i) Composite material. Due to the excellent electrical conductivity and Fe 3 O 4The magnetic permeability of FCP&M and SGFCP&M composite materials is higher than 50.0dB, which fully meets the main demand of commercial EMI shielding of 20dB. In addition, the EMISET of FCP&M and SGFCP&M composite materials in the x-band continues to increase with the increase of printed layers. The maximum EMISET of FCP&M-4 can reach 57.1dB. With the increase of the number of layers, the maximum EMISET of FCP&M-10 increases moderately to 70.4dB. Figure 3 In addition, the EMISET of SGFCP&M-10 is slightly better than that of FCP&M-10 with the same number of layers, with a maximum value of 72.5dB, which fluctuates slightly with frequency in the x-band, as shown in Figure 3 f. Similarly, the average SE of SGFCP&M and FCP&M composites T , SE R and SE A And the power coefficient A and R are as follows Figure 3 (h) Figure 3 (k) and Figure 3 (l) As shown in Figure 1, it can be clearly seen that the average SET and SEA of SGFCP&M and FCP&M composite materials gradually increase with the increase of printed layers. Especially at the 10th layer, the average SET of SGFCP&M-10 and FCP&M-10 is greatly improved to 67.7dB and 65.1dB, respectively. Figure 3 (g) and Figure 3 (k) As shown. With the same number of layers, the average SET of SGFCP&M is slightly higher than that of FCP&M, indicating that the single gradient structure is superior to the uniform structure in improving EMISE. However, the SER of FCP&M and SGFCP&M composites decreases slightly with the increase of the number of layers, but does not exceed 7.0 dB, which is due to the improved impedance matching between adjacent layers and the thickening of the porous structure. Therefore, SE T The enhancement is mainly due to SE A The rise instead of SE R This is attributed to the increase of mobile carriers and electromagnetic synergy.
[0096] In addition, the A of FCP&M and SGFCP&M frameworks visually shows an increasing trend with the increase of the number of layers, while the R of the composite framework shows the opposite trend, e.g. Figure 3(h). It is worth noting that the A (<0.5) of all FCP&M frameworks is significantly smaller than R (>0.5), indicating that the shielding principle of the homogeneous FCP&M composite is mainly reflection. It is worth noting that the A of SGFCP&M-8 and SGFCP&M-10 are 0.52 and 0.55, respectively, which are slightly larger than their respective R, indicating the obvious advantage of EMW absorption. However, at the same number of layers, the SET-12 and A-12 of the DGFCP&M framework are larger than the SET-12 and A-12 of the SGFCP&M and FCP&M composite frameworks, which shows that the "lattice-filler" lattice filling dual gradient design strategy has great advantages for manufacturing excellent light-absorbing EMI shielding composites with absorption as the main factor.
[0097] according to Figure 3 (b)- Figure 3 (d) SE of DGFCP&,My composite material with double gradient structure in X-band T The maximum value can reach 76.9dB, and the average absorption coefficient A can reach 0.62. Compared with the single lattice gradient SGFCP&M-y composite framework, SE T The average absorption coefficient A significantly increased by about 14%, and the average absorption coefficient A significantly increased by about 13%. This is due to the continuous optimization of the impedance matching layer on the surface of the dual gradient structure, which further reduces the reflection of electromagnetic waves on the incident interface. At the same time, the dual gradient structure composite material is reasonably designed to achieve the best interface matching of absorption, reflection and reabsorption between the top layer, the middle layer and the bottom layer, and the carbon nanotube content in each layer is customized to maximize EMI shielding and improve absorption efficiency. It should be noted that the average absorption coefficient A of the DGFCP&M-y lightweight composite material increases from 0.28 to 0.62, and then slowly drops to 0.56 as the number of layers increases. When the number of layers y ≥ 6 (average thickness ≥ 1.25mm), the electromagnetic shielding of the composite frame becomes a loss mechanism dominated by absorption, which is significantly better than single lattice size single gradient and non-gradient uniform structure composite materials. This may be because as the number of printed layers increases, the thickness and density of the material increase, which improves the magnetic and conductive networks and promotes the rapid improvement of the absorption efficiency of electromagnetic waves. However, when the number of printing layers increases further, the porosity and internal cavities of the dual gradient structure reduce the density of the material, which may weaken the ability to absorb electromagnetic waves and cause the absorption coefficient A to slowly decrease.
[0098] In summary, the present application provides a high-performance electromagnetic interference (EMI) shielding flexible composite material with excellent mechanical properties and absorption as the main feature, which adopts immersion deposition multi-nozzle 3D printing technology to continuously and accurately control the printing wire spacing, i.e., the lattice scale, from bottom to top in the solidification bath, and adjust the Fe 3 O 4The CNT content in the / CNT / PU composite ink obtains a porous composite framework, which is further bonded and assembled with a highly conductive flexible MXene film to obtain a high-absorption electromagnetic shielding composite material with a gradient structure, achieving high EMI shielding with an asymmetric adjustable absorption coefficient and excellent mechanical properties.
[0099] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0100] In addition, it should be understood that although the present specification is described according to embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that those skilled in the art can understand.
Claims
1. A 3D printing preparation method for a high-absorption electromagnetic shielding composite material with a gradient structure, characterized in that: The preparation method comprises: Step 1: Preparation and collection of Fe3O4 / CNT / PU composite ink: Add Fe3O4 and CNT into dimethyl sulfoxide solution, shake well and perform ultrasonic dispersion for 25-35 min, then add TPU particles, and continuously stir mechanically for 11-13 hours at room temperature to obtain Fe3O4 / CNT / PU composite ink. Add different CNT contents as needed to prepare various Fe3O4 / CNT / PU composite inks; Step 2: Preparation of a composite frame with a porous structure: The various Fe3O4 / CNT / PU composite inks prepared above are sequentially input into a 3D printer for extrusion printing in a coagulation bath to obtain a composite frame with a three-dimensional gradient structure, and the composite frame is soaked and rinsed with deionized water, and then dried at a constant temperature to obtain a composite frame with a porous structure; Step 3: Preparation of a high-absorption electromagnetic shielding composite material with a gradient structure: The composite frame with a porous structure prepared above is bonded and cured using a polyurethane solution and a highly conductive flexible MXene film obtained by vacuum filtration to obtain a high-absorption electromagnetic shielding composite material with a gradient structure.
2. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1, characterized in that: The composite frame is formed by stacking multiple structural frames with different lattice scales from bottom to top, and the lattice scales of the multiple structural frames show an increasing trend in sequence. Each of the structural frames is made of the Fe3O4 / CNT / PU composite ink with one CNT content through immersion precipitation 3D printing, and the CNT content of each Fe3O4 / CNT / PU composite ink shows a decreasing trend in sequence. The highly conductive and flexible MXene film is bonded to the bottom of the composite frame and is located on the surface of the side where the structural frame with the smallest lattice scale is located.
3. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1 or 2, characterized in that: The composite frame is soaked and rinsed with ionized water at least 2 to 3 times.
4. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1, characterized in that: The composite frame is dried at a constant temperature for at least 10 hours, and the temperature range of the constant temperature is 32° C. to 45° C.
5. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1, characterized in that: The lattice scale difference between two adjacent structural frames ranges from 0.05 mm to 1 mm.
6. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1, characterized in that: The method for preparing the highly conductive flexible MXene film comprises the following steps: (1) LiF and hydrochloric acid are mixed and placed in a water bath with a temperature of ≤42°C with magnetic stirring; (2) Add Ti3AlC2 powder and raise the temperature to ≥45°C, and continue stirring for 48 to 72 hours; (3) centrifuging the reaction solution at 4500-5500 rpm for ≥2 min and removing the supernatant; (4) adding hydrochloric acid, ultrasonically treating for ≥5 min and centrifuging for a second time at 4500-5500 rpm, washing with water and centrifuging for ≥5 times, and the solution is neutral, i.e., pH ≥5. After the reaction is completed, placing in an ice water bath and ultrasonically dispersing for ≥2 h; (5) high-speed centrifuging the MXene solution obtained in step (4) to obtain a dispersion of few-layer MXene nanosheets; (6) The few-layer MXene nanosheet dispersion obtained in step (5) is subjected to vacuum-assisted filtration to prepare the highly conductive and flexible MXene film.
7. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1 or 6, characterized in that: The average thickness of the flexible MXene film is 12 μm, and the electrical conductivity is 3.1×10 5 S / m.
8. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1, characterized in that: The mass ratio of the Fe3O4, CNT and TPU particles is 1:0 to 1:8.5 to 9.
5.
9. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 1 or 8, characterized in that: The CNT content in the Fe3O4 / CNT / PU composite ink is 0wt% to 8.9wt%.
10. The 3D printing preparation method of the high absorption electromagnetic shielding composite material with gradient structure according to claim 2, characterized in that: The conductivity variation range between two adjacent structural frames is 1×10 -8 ~3.1×10 5 S / m.
Citation Information
Patent Citations
Double-shielding structure material with directional electromagnetic shielding performance and preparation method thereof
CN113442520A
Low-reflection and high-absorption porous electromagnetic shielding device and preparation method thereof
CN113561473A
Polyurethane foam material as well as preparation method and application thereof
CN116333251A
Electromagnetic shielding composite film with gradient structure and preparation method thereof
CN117841501A
Polyurethane / non-woven electromagnetic shielding material and preparation method thereof
CN118065128A
Cited By
Core-shell structure fiber with strain-insensitive conductive characteristic and electromagnetic wave absorption-reflection cycle loss mechanism as well as preparation method and application of core-shell structure fiber
CN122279804A
Core-shell structure fiber with strain-insensitive conductive property and electromagnetic wave absorption-reflection cyclic loss mechanism, and preparation method and application thereof
CN122279804B